Analysis of factors that influence on ethical considerations of future accountants - Husna Roza; Elvira Luthan (Proceeding International Conference on Accounting and Finance, 2023)
This study aims to identify various factors that influence the ethical considerations of future accountants in West Sumatra. Primary data is used and the respondents are the last accounting students in the area. The research questionnaire used is modifications of several previous studies. Before performing multiple regression analysis, the author has tested the quality of the data, and tested the classical assumption. The conclusions from hypothesis show that the ethical content in teaching accounting and emotional intelligence have a significant and positive influence on the ethical considerations of future accountants. While the orientation, both the dimensions of idealism and the dimensions of relativism have no effect. This study fills the gaps in research on ethical orientation, emotional intelligence and ethical content in accounting teaching about ethical considerations, and it is useful for providing information in making decisions related to ethics, which in turn will increase credibility of future accountants.